Private Higher Education’s Distinctive Niche in New Zealand - Abbot, Malcolm (International Higher Education, 2015)
Private higher education plays a small but distinctive role in New Zealand higher education, providing, for example, educational opportunities for minority groups. Private provision of higher education has been controversial politically.